Composite fibers prepared from multi-walled carbon nanotubes/cellulose dispersed/dissolved in ammonium/dimethyl sulfoxide mixed solvent. Issue 4 (12th January 2017) - Jiang, Zeming; Chen, Danni; Yu, Yongqi; Miao, Jiaojiao; Liu, Yang; Zhang, Liping
Abstract : A co-dispersion of cellulose and MWCNTs was prepared in a TBAA/DMSO solvent mixture and then used to prepare composite fibers. Abstract : A co-dispersion of cellulose and multi-walled carbon nanotubes (MWCNTs) was prepared in a tetrabutylammonium acetate/dimethyl sulfoxide solvent mixture, to yield hydroxide radical functionalized-MWCNTs. The rheological properties of the mixture were investigated, and its morphology was investigated by optical microscopy. The mixture was then used to prepare composite fibers by a dry-wet spinning process at room temperature. The regenerated composite fibers prepared by coagulation in water were characterized by scanning electron microscopy, X-ray diffraction, Fourier-transform infrared spectroscopy, thermogravimetric analysis, and electronic tensile testing and four-probe testing measurements. The results showed that the mixture was well dispersed, with good interaction between the cellulose and MWCNTs. Introducing an appropriate amount of MWCNTs could enhance the crystallinity, thermal stability, mechanical properties, and electrical conductivity of the composite fibers.